Unconditional self-acceptance among Baghdad University students - Ne’meh Hindi, Hussain; Al-Araji, Ibrahim Mortadha (Al-Adab Journal, 2020)
That Unconditional self-acceptance is the complete acceptance of one’s self without restriction or condition, whether he behaves smartly or not, regardless of the nature of behavior, achievement, approval, respect or love from others. The current research aims to identify: 1- Unconditional self-acceptance for Baghdad University students 2 - The significance of the difference in unconditional self-acceptance according to gender variables (male - female) and specialization (scientific – human ) . 3- The relationship between unconditional self-acceptance and the tendency towards perfection among Baghdad University students. The researcher has prepared an unconditional self-acceptance scale, and the scale may be of (22) paragraphs of the measur were analyzed statistically and the validity and reliability indicators were calculated for them. The measur were applied to a sample of (400) students from the University of Baghdad and the data were statistically analyzed using the ANOVA T test and the Pearson correlation coefficient at the significance level( 0,05) The research summarized the following results 1- The members of the research sample are characterized by unconditional self-acceptance 2- There are no statistically significant differences in the unconditional self-acceptance of Baghdad University students according to the two sex variables (males, females) 3- The relationship between unconditional self-acceptance and the tendency towards perfection is an inverse relationship.